Main-chain mutagenesis reveals intrahelical coupling in an ion channel voltage-sensor. Issue 1 (December 2018) - Infield, Daniel; Matulef, Kimberly; Galpin, Jason; Lam, Kin; Tajkhorshid, Emad; Ahern, Christopher; Valiyaveetil, Francis
Abstract Membrane proteins are universal signal decoders. The helical transmembrane segments of these proteins play central roles in sensory transduction, yet the mechanistic contributions of secondary structure remain unresolved. To investigate the role of main-chain hydrogen bonding on transmembrane function, we encoded amide-to-ester substitutions at sites throughout the S4 voltage-sensing segment ofShaker potassium channels, a region that undergoes rapid, voltage-driven movement during channel gating. Functional measurements of ester-harboring channels highlight a transitional region between α-helical and 310 segments where hydrogen bond removal is particularly disruptive to voltage-gating. Simulations of an active voltage sensor reveal that this region features a dynamic hydrogen bonding pattern and that its helical structure is reliant upon amide support. Overall, the data highlight the specialized role of main-chain chemistry in the mechanism of voltage-sensing; other catalytic transmembrane segments may enlist similar strategies in signal transduction mechanisms. The helical transmembrane segments of membrane proteins play central roles in sensory transduction but the mechanistic basis for their function remains unresolved. Here the authors identify regions in the S4 voltage-sensing segment ofShaker potassium channels where local helical structure is reliant upon backbone amide support.